Intellectual Origins of Islamic Resurgence in the Modern Arab World - Charles D. Smith (International Institute of Islamic Thought, 1996)
Most studies of Islamist resurgence have focused on specific aspects of the Islamist political agenda and have sought to identify their intellectual roots in the writings of thinkers from the medieval period of Islamic history. Influenced by Iran’s Islamic revolution, these authors have been concerned primarily with political Islam. It is rare to find a book that seeks to establish modem Islamist thought within the context of western critical theory and indigenous political conditions, or that explains its ideas in light of a conflict between revolutionary discourse and state hegemony. Abu-Rabi”s book is thus all the more welcome, as it establishes a basis for consideration of Islamist thinkers that will be an essential reference in the fbtwx. The subject of this book is the thought of Sayyid Qqtb, considered within the parameters of Islamic modernism, westernization, orientalism, and the contemporary Islamist response to these factors. Abu-Rabi‘ says he is undertaking an intellectual history of his subject, that of “a popular religious movement . . . founded by lay Muslim intellectuals” often at odds with the traditional political and religious elites. But he considers this question in light of the “question of continuity and discontinuity in modem Arab thought.” Influenced by Foucault, he argues that the question of epistemological acts and thresholds, of conceptual ruptures in the development of ideas, must be countered by the reality of continuities in Islamic thought, by the fact of an ongoing Islamic discourse whose exposition may change according to historical circumstances but whose essence and focus of concern remain constant (pp. 5-6). The idea of continuity and discontinuity is a valuable method for considering various themes in Arab thought, ranging from the liberal thinkers of the nuhdah (renaissance) to both secular and religious Arab responses to the challenge of colonization and the question of how best could Arab- Islamic societies survive foreign occupation. Essential here is the question of Arab Muslim “decline,” how and why it occurred, and how this decline may be reversed. Abu-Rabi‘ surveys a variety of Muslim thinkers to posit three approaches to the relevance of Islamic tradition to the resolution of the problem of decline: the rejection of tradition in favor of intellectual stimulus from the West; a conservative approach calling for the “revival of ...